Kapabilitas Belajar dalam Proses Pembelajaran (Kajian Konsep Teori Gagne dalam Praktek Pembelajaran) - Moh Sutomo (FALASIFA : Jurnal Studi Keislaman, 2017)
Understanding the meaning of learning and teaching will not be enough for a learner (teacher) to succeed in performing the task as a teacher if we do not understand the results of learning well. Learning outcomes are often referred to as learning capability is the impact of learning process conducted by the learners and teaching conducted by learners. By understanding the categories of learning capabilities that the study wants to do, it will affect the different learning methods by the learners in the learn. These different learning methods lead to differences and changes in the management of the learning experience. The accuracy in understanding the learning capability cagorization that the learning wants to achieve will lead to accuracy in choosing the method and ultimately impact on the effectiveness of the learners in achieving the learning capabilities they want.Â Keywords: Kapabiltas Belajar Dalam Proses Pembelajaran